2011
DOI: 10.22256/pubvet.v5n5.1022
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação de coliformes totais e termotolerantes em queijo Minas Frescal artesanal

Abstract: ResumoForam analisadas vinte amostras de queijo Minas Frescal obtidas em feiraslivres da cidade de Uberlândia-MG, durante o período de outubro a novembro de 2006. A análise microbiológica constituiu-se da contagem de coliformes totais e fecais ou termotolerantes, através do NMP (Número Mais Provável), onde 14 das amostras analisadas (70%) apresentaram NMP de coliformes totais superiores a 10 3 NMP/g e 16 das amostras analisadas (80%) apresentaram NMP de coliformes termotolerantes superiores a 10 2 NMP/g. De ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
1
4
0
8
Order By: Relevance
“…The presence of thermotolerant coliforms in cheese from hotel 3 suggests the use of low-quality raw materials, inadequate processing conditions, poor hygiene practices by handlers, or inadequate storage and transportation. Comparable results were also found by Ferreira et al (2011) upon analyzing 20 samples of minas frescal cheese obtained from street markets in the city of Uberlândia, Brazil. The authors found that 80% of the samples were above legal acceptable thermotolerant coliform count limits.…”
Section: Resultssupporting
confidence: 57%
“…The presence of thermotolerant coliforms in cheese from hotel 3 suggests the use of low-quality raw materials, inadequate processing conditions, poor hygiene practices by handlers, or inadequate storage and transportation. Comparable results were also found by Ferreira et al (2011) upon analyzing 20 samples of minas frescal cheese obtained from street markets in the city of Uberlândia, Brazil. The authors found that 80% of the samples were above legal acceptable thermotolerant coliform count limits.…”
Section: Resultssupporting
confidence: 57%
“…In the Alto Paranaíba microregion, Fernandes et al (2011) found that all cheeses analyzed had microbiological standards outside of the legislation and, therefore, were prohibited for human consumption. In the microregion of Triângulo, Ferreira et al (2011) found that 70% of the analyzed cheese samples were above the legal parameters for total coliforms at 30°C and 80% for thermotolerant coliforms (coliforms at 45°C…”
Section: Conformitymentioning
confidence: 99%
“…Porém, para que a maturação seja eficiente na segurança microbiológica, são necessárias condições satisfatórias de higiene antes, durante e após a fabricação do queijo, evitando uma alta contaminação inicial ou uma recontaminação do produto através de treinamentos e Boas Práticas de Fabricação (BPF) (TEODORO et al, 2013a;FERREIRA et al, 2011;PINTO et al, 2009a). A qualidade da água e do leite utilizados, o controle de pragas e vetores, a limpeza de utensílios e superfícies, a higienização correta das mãos, unhas cortadas e barbas aparadas, o uso de uniformes, e o correto armazenamento e transporte dos produtos são práticas importantes para o controle de qualidade, prevenindo a disseminação de patógenos (MALAGUETA JÚNIOR et al, 2012;MACHADO et al, 2009;MELLO et al, 2010;FERREIRA et al, 2013).…”
Section: Resistência De Bactérias Patogênicas Ao Processo De Maturaçãunclassified